Active labour market policy in the European Union - Klaus Schömann (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1995)
This report deals with Action 5 of the White Paper Follow-Up process and analyses feasible steps or improvements already undertaken by Member States and the Community at large to make better use of public funds for combating unemployment. Public funds devoted to labour market policies play a vital role in achieving employment intensive growth. The White Paper on Growth, Competitiveness and Employment of the Commission of the European Communities proposes a full-scale overhaul of employment policies and a shift of the balance of public expenditure decisively in favour of active labour market policies. Part one of the report approaches in a more analytical way the dynamics of active labour market policies in the Member States. On the basis of the concept of active versus passive expenditure the current balance and recent shifts in this balance are compared across European Union Member States. Along the line of OECD-definitions and data collection efforts of active and passive public expenditure a comparative assessment of overall public expenditure and selected subject areas is accomplished. Particular attention is devoted to (1) funds allocated to public employment services, (2) public expenditure devoted to the integration of the young and (3) the long-term unemployed. – – In diesem Bericht werden jüngste Entwicklungen im Bereich der Arbeitsmarktpolitik in den Mitgliedsländern der E.U. aufgezeigt. In einer ersten Bestandsaufnahme wird untersucht, inwiefern die Empfehlungen des Weißbuchs für Wachstum, Wettbewerb und Beschäftigung in den Mitgliedsländern bereits Anwendung finden. Das Weißbuch hatte ein Überdenken der Arbeitsmarktpolitik in den Mitgliedsländern angeregt mit der eindeutigen Maßgabe, öffentliche Ausgaben mehr für aktive Arbeitsmarktpolitik zu verwenden. Im ersten Teil des Berichts wird die Dynamik in den Ausgaben für aktive Arbeitsmarktpolitik analysiert auf der Basis der OECD-Unterscheidung von aktiven und passiven öffentlichen Ausgaben. Besondere Schwerpunkte der vergleichenden Untersuchung bilden: (1) die Ausgaben für die öffentliche Arbeitsverwaltung, (2) Aufwendungen für die Integration von Jugendlichen und (3) Langzeitarbeitslosen.
Keywords: 330